Stability of Red Color Rosella Extract for Food and Beverage Colorant - Winarti, Sri; Firdaus, Abdurrozaq (Jurnal Teknologi Pertanian, 2010)
Natural dye (pigment) is naturally present in plants and animals. Natural dyes can be classified as green, yellow, and red. Red dye obtained from extract of rosella flowers is very potential as food and beverage colorant. However, the suitable solvents for extraction and the stability the extract to pH, sugar, salt, heating and in some foods and beverages was still unknown.  The purpose of this study was to determine the most suitable solvent for the extraction of red pigment in flower calyx and to know the stability of the extract on various conditions.  The study consisted of two steps: rosella pigment extraction with water : acetic acid : ethanol in ratios of 1:0:0, 2:1:2, 1:0:1, and 2:0:1; and the test of color stability of red rosella on various pH, sugar, salt, heating temperature, heating time, that resemble to food products or beverages.  The results showed that the best treatment was extraction of dyes with solvent water: acetic acid: ethanol = 1:0:0 that produced extract with anthocyanin content of 3.07%. Red colorant from rosella extract is less stable to pH changes.  The changes in sugar levels was stable at up to 50%, stable in salt levels up to 10%, less stable at temperatures up to 100 °C and heating time up to 90 minutes.Keywords: red color, stability, rosella extract